1992
DOI: 10.1002/ar.1092320209
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the endocrine cells in the pancreatic‐bile duct system of the rat

Abstract: Six types of endocrine cells showing immunolabelling against gut or pancreatic islet hormones were identified in the pancreatic-bile duct system of the normal adult rat at the light and electron microscopic levels. They were located within the epithelial lining of the duct system from the intercalated portion to its duodenal opening. However, the distribution and frequency of each endocrine cell varied along the length of the duct system. While insulin, glucagon, somatostatin, and pancreatic polypeptide cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 40 publications
1
19
0
1
Order By: Relevance
“…On the other hand, this exocrine secretion of an hormone is not a unique phenomenon since all the other islet hormones have been previously reported in rat PJ (Prinz et al 1978, Ertan et al 1981, Bertelli et al 2001. Moreover, since some endocrine cells are of the open type facing the duct lumen, as previously reported (Park & Bendayan 1992), they could provide a direct pathway for Agt secretion into the ducts. An accidental plasmatic source for the PJ Agt should be excluded for two reasons: the constant finding of Agt in the PJ from all examined animals which should exclude occasional contaminations; and the different patterns of isoforms identified by IEF occurring between plasma and PJ Agt, demonstrating separate origins.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…On the other hand, this exocrine secretion of an hormone is not a unique phenomenon since all the other islet hormones have been previously reported in rat PJ (Prinz et al 1978, Ertan et al 1981, Bertelli et al 2001. Moreover, since some endocrine cells are of the open type facing the duct lumen, as previously reported (Park & Bendayan 1992), they could provide a direct pathway for Agt secretion into the ducts. An accidental plasmatic source for the PJ Agt should be excluded for two reasons: the constant finding of Agt in the PJ from all examined animals which should exclude occasional contaminations; and the different patterns of isoforms identified by IEF occurring between plasma and PJ Agt, demonstrating separate origins.…”
Section: Discussionmentioning
confidence: 56%
“…In addition, Agt may also be secreted into the excretory ducts through the multiple connections occurring between the endocrine compartment of the pancreas and the ductal tree (Park & Bendayan 1992, Bertelli et al 1994). This secretion could be favoured by the peripheral location of glucagon-secreting cells, since duct-islet contacts prevalently take place at the edge of the islets (Bertelli et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed studies carried out on adult rat pancreas have shown that all four major types of pancreatic endocrine cells [i.e., glucagon-, insulin-, somatostatin-and pancreatic polypeptidesecreting (PP) cells] can be found as single cells intermingled with duct cells (Park and Bendayan 1992;Bertelli et al 1994). In addition, distal to the confluence of the pancreatic and bile duct systems (i.e., in the common pancreatic-bile duct), serotonin-and cholecystokinin (CCK)-containing cells can also be observed (Park and Bendayan 1992). Remarkably, in diabetic animals CCK-and somatostatin-immunoreactive cells located in the common pancreatic-bile duct double in number (Park and Bendayan 1994).…”
Section: Single Endocrine Cellsmentioning
confidence: 99%
“…This observation acquires importance because somatostatin has been reported to influence the tonus of Oddi's sphincter (Ahrendt et al 1992;Binmoeller et al 1992) and also because islets of Langerhans containing somatostatin-secreting cells have been demonstrated in the submucosal layer of the duodenum close to the Oddi's sphincter Park 1991,1997), where the epithelium of the common bile duct is also rich in somatostatin-containing cells (Park and Bendayan 1994). In normoglycemic animals, the topographical distribution of the four types of islet cells scattered within the epithelium displays an almost even distribution of insulin-and glucagon-producing cells along the entire duct tree, whereas the incidence of PP and somatostatin-secreting cells gradually increases toward the more distally located portions of the duct system (Park and Bendayan 1992). Most of these endocrine cells are classified as "open type" cells, because they face the duct lumen with a variable area of cell surface (Figure 1).…”
Section: Single Endocrine Cellsmentioning
confidence: 99%
“…Obtaining information about the 3D structure of both endocrine and exocrine components of the pancreas simultaneously has great potential value, because of the systematic and complex physical, topographical, and functional associations between these components, which can reflect pathological changes. 13,19 …”
Section: Organization Of the Endocrine Pancreasmentioning
confidence: 99%